The Iraqi constitution and the principles of the work of the Supreme Administrative Court - abduladheem alwash, Lamyaa haleem (Opción, 2019)
The administrative judiciary monitors the validity of the orders and decisions issued by the executive authority as the administration and makes sure that the de- cision or administrative order was issued in accordance with the law. The administrative judiciary in this way is considered legitimate. It ensures that the administration does not violate the law when issuing its decisions. This is what fulfills the principle of the rule of law over both the ruler and the ruled. However, the administrative judiciary and any judicial body must comply with the law in its work. If he violates the ordinary law, he must neglect the text of the ordinary law and implement the constitutional text, and so on. However, some of our adminis- trative decisions have either ignored or ignored the principle of incorporation of legal norms.